Filoviruses A Compendium of 40 Years of Epidemiological, Clinical, and Laboratory Studies - Kuhn, Jens. (Archives of Virology. Supplementa,, 2008)
The filoviruses (Lake Victoria marburgvirus and ebolaviruses) are etiological agents of severe hemorrhagic fevers with extraordinary high case-fatality rates for humans, chimpanzees, gorillas, and probably other animals. Many institutions and experts consider them as potential threats to humanity because they could be used as biological weapons. This book summarizes in detail the contemporary knowledge of filoviruses and diseases they cause. Almost the entirety of the open literature on filoviruses, covering all major scientific and clinical fields, is referenced and summarized in this text, including most of the conference abstracts, book chapters, dissertations, government reports, patents, theses, and journal publications in many languages. The book will provide a robust source of knowledge for filovirologists, virologists and scientists in general, clinicians, students, journalists, and biodefense professionals.  .